2003
DOI: 10.1164/rccm.200208-855oc
|View full text |Cite
|
Sign up to set email alerts
|

Significant Microbiological Effect of Inhaled Tobramycin in Young Children with Cystic Fibrosis

Abstract: We conducted a double-blind, placebo-controlled, multicenter, randomized trial to test the hypothesis that 300 mg of tobramycin solution for inhalation administered twice daily for 28 days would be safe and result in a profound decrease in Pseudomonas aeruginosa (Pa) density from the lower airway of young children with cystic fibrosis. Ninety-eight subjects were to be randomized; however, the trial was stopped early because of evidence of a significant microbiological treatment effect. Twenty-one children unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
211
2
15

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(231 citation statements)
references
References 50 publications
3
211
2
15
Order By: Relevance
“…Therefore, these results suggest that the direction of migration is mainly downwards at the early stages of infection. If it is assumed that recurrent intermittent lung colonization with the same genotype is associated with persistent sinus colonization, ours and other studies show that around 25% of the CF children may begin with a sinus colonization (Munck et al, 2001;Gibson et al, 2003;Doring et al, 2006), and more than half of all patients will eventually be affected (Mainz et al, 2009). The study further shows that phenotypic and genotypic changes observed in sinus isolates of P. aeruginosa are similar or identical to those often reported for isolates from chronic lung infections in CF patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, these results suggest that the direction of migration is mainly downwards at the early stages of infection. If it is assumed that recurrent intermittent lung colonization with the same genotype is associated with persistent sinus colonization, ours and other studies show that around 25% of the CF children may begin with a sinus colonization (Munck et al, 2001;Gibson et al, 2003;Doring et al, 2006), and more than half of all patients will eventually be affected (Mainz et al, 2009). The study further shows that phenotypic and genotypic changes observed in sinus isolates of P. aeruginosa are similar or identical to those often reported for isolates from chronic lung infections in CF patients.…”
Section: Discussionmentioning
confidence: 59%
“…The early stages of lung disease have therefore been recognized as windows of opportunity to eradicate P. aeruginosa (Burns et al, 2001), and clinical trials have shown that early aggressive treatment is beneficial for the patient and delays transition into a chronic infection (Høiby et al, 2005;Taccetti et al, 2005). Following eradication, a new acquisition is often with a different genotype, but some studies have shown that in approximately 25% of the cases re-colonization occurs with the same genotype of P. aeruginosa (Munck et al, 2001;Gibson et al, 2003;Doring et al, 2006). Re-colonization could be either from a persistent environmental source or from an undetected reservoir in the patient upper airways such as the paranasal sinuses (Jelsbak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no controlled trials of this approach in PCD. If P. aeruginosa is isolated, most clinicians would prescribe an eradication regimen similar to those used in CF, and, for established chronic infection with this organism, long-term nebulised antipseudomonal antibiotics are considered, but evidence of efficacy has yet to be gathered in PCD patients [91][92][93].…”
Section: Respiratory Treatmentmentioning
confidence: 99%
“…The les is characterized by resistance to ceftazidime, but it is susceptible to tobramycin and ciprofloxacin 65 . It is stressed that early aggressive antibiotic therapy using inhaled antibiotics either as monotherapy (tobramycin) 81 or inhaled antibiotics in combination with oral antibiotics (colistin and ciprofloxacin) 82 is important to prevent or delay chronic P. aeruginosa infection. It has been shown that early treatment can slow the decline of pulmonary function after initial colonization with P. aeruginosa 82 …”
Section: Managementmentioning
confidence: 99%